The International Politics of Ebola
DOI: 10.4324/9781138293588-8
|View full text |Cite
|
Sign up to set email alerts
|

The race for Ebola drugs: pharmaceuticals, security and global health governance

Abstract: The international Ebola response mirrors two broader trends in global health governance: (1) the framing of infectious disease outbreaks as a security threat; and (2) a tendency to respond by providing medicines and vaccines. This article identifies three mechanisms that interlink these trends. First, securitisation encourages technological policy responses. Second, it creates an exceptional political space in which pharmaceutical development can be freed from constraints. Third, it creates an institutional ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Earlier disease outbreaks have been coined in security terms by employing wartime discourse. This happened during outbreaks of Ebola (Roemer‐Mahler & Elbe, 2016; Walsh & Johnson, 2018), Asian influenza (Curley & Herington, 2011), Zika (Wenham & Farias, 2019), pandemic influenza (Kamradt‐Scott & McInness, 2012; Watterson & Kamradt‐Scott, 2016) and in response to the spread of HIV/AIDS (Sjöstedt, 2008). And if there is an “enemy” to be “fought” in “battle” or “war,” which organization would be better suited to take the lead than the military?…”
Section: Explanation Of Large‐scale Military Deployments During Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier disease outbreaks have been coined in security terms by employing wartime discourse. This happened during outbreaks of Ebola (Roemer‐Mahler & Elbe, 2016; Walsh & Johnson, 2018), Asian influenza (Curley & Herington, 2011), Zika (Wenham & Farias, 2019), pandemic influenza (Kamradt‐Scott & McInness, 2012; Watterson & Kamradt‐Scott, 2016) and in response to the spread of HIV/AIDS (Sjöstedt, 2008). And if there is an “enemy” to be “fought” in “battle” or “war,” which organization would be better suited to take the lead than the military?…”
Section: Explanation Of Large‐scale Military Deployments During Covid‐19mentioning
confidence: 99%
“…And if there is an “enemy” to be “fought” in “battle” or “war,” which organization would be better suited to take the lead than the military? During the Ebola crisis, Liberia and Sierra Leone activated their armed forces, while Western governments likewise deployed thousands of military units (Roemer‐Mahler & Elbe, 2016). In response to the Zika crisis, the Brazilian military was also sent onto the streets to “combat” the “enemy,” while simultaneously signalling the gravity of the situation to the population (Wenham & Farias, 2019).…”
Section: Explanation Of Large‐scale Military Deployments During Covid‐19mentioning
confidence: 99%
“…Political concern with health security often also goes hand in hand with the pharmaceuticalization of public health threats, where pursuit of “magic bullet” interventions can eclipse political engagement with the underlying socioeconomic issues that contribute to the causes of the crisis (Davies 2008 ). A pharmaceutical intervention focusing on “a precise target in a circumscribed event with direct security relevance for domestic populations” will be an easier sell politically than a long-term commitment to addressing “complex socioeconomic problems whose domestic relevance is uncertain” (Roemer-Mahler and Elbe 2016 , 493). Moreover, where a health security threat has been identified, an “exceptional policy space” opens up in which key norms and rules governing the development and approval of pharmaceutical interventions can be modified to expedite an effective and politically acceptable response to the threat (Roemer-Mahler and Elbe 2016 , 495; Edwards 2013 ).…”
Section: Part I: Four Conditions Of Global Health Crisis Decision-makmentioning
confidence: 99%
“…Yet this does not mean old Pharmaceuticals and the Global South 371 debates have disappeared. Echoes of the earlier dependency debate have re-emerged with renewed emphasis on local production, and as growing discourses of health security and insecurity (Nunes 2014, Roemer-Mahler andElbe 2016), and on interdependence (Frenk et al 2014), are mobilised in a more globalised world. The pharmaceutical industry has now become more differentiated.…”
Section: Crossing Development Boundaries: Health and Industrymentioning
confidence: 99%
“…Moon et al () have suggested the need to delink the financing from the pricing of products and have proposed an international R&D treaty in this regard. Health crises, for example that posed by the Ebola outbreak, have also raised questions for global governance, including response to infectious diseases and questions of new medicines development (Roemer‐Mahler and Elbe ).…”
Section: Crossing Development Boundaries: Health and Industrymentioning
confidence: 99%